2017
DOI: 10.1002/cta.2435
|View full text |Cite
|
Sign up to set email alerts
|

A new non‐isolated free ripple input current bidirectional DC‐DC converter with capability of zero voltage switching

Abstract: Summary In this paper, a new nonisolated free ripple input current bidirectional dc‐dc converter with capability of zero voltage switching (ZVS) is proposed. The free ripple input current condition at low voltage side is achieved by using third winding of a coupled inductor and a capacitor for the whole range of duty cycles. In the proposed structure, the voltage conversion ratio can be more increased by adding the turn ratio of the second winding of the coupled inductor for the whole range of duty cycles. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 28 publications
1
55
0
Order By: Relevance
“…It can be seen that in operation at the duty cycle range 1/3 ≤ D < 2/3, the maximum current ripple value of the proposed topology is 0.0083 occurs at D = 1/2, where this value is one‐third compared with Jin and Liu 23 and half value compared with Bal et al 51 While in operation at duty cycle range 2/3 ≤ D < 1, the current ripple of studied topology is higher than that of the converter in Bal et al 52 ; when the duty cycle is equal to 5/6, and the normalized current ripple is equal to 0.0083. Furthermore, the current ripple of the previously proposed converters in previous studies 26 , 51 is higher than that of the proposed topology, according to the values shown in Figure 12A. Also, the normalized current ripple cancellation of the proposed topology occurs when the duty cycle is 1/3 and 2/3, which means that the proposed topology has a better dynamic response and smaller size inductor.…”
Section: Mathematical Analyses and Fundamental Equationsmentioning
confidence: 82%
“…It can be seen that in operation at the duty cycle range 1/3 ≤ D < 2/3, the maximum current ripple value of the proposed topology is 0.0083 occurs at D = 1/2, where this value is one‐third compared with Jin and Liu 23 and half value compared with Bal et al 51 While in operation at duty cycle range 2/3 ≤ D < 1, the current ripple of studied topology is higher than that of the converter in Bal et al 52 ; when the duty cycle is equal to 5/6, and the normalized current ripple is equal to 0.0083. Furthermore, the current ripple of the previously proposed converters in previous studies 26 , 51 is higher than that of the proposed topology, according to the values shown in Figure 12A. Also, the normalized current ripple cancellation of the proposed topology occurs when the duty cycle is 1/3 and 2/3, which means that the proposed topology has a better dynamic response and smaller size inductor.…”
Section: Mathematical Analyses and Fundamental Equationsmentioning
confidence: 82%
“…Besides, it also limits the voltage gain and increases the normalized voltage stress on semiconductors, so conventional boost converters are not proper for high power ranges [4]. As a result, the overall efficiency will be decreased and also electromagnetic interference (EMI) will be a big problem [5]. To obtain a high voltage level at the output side of dcdc converters with high efficiency and high power level, more methods are proposed by researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of interleaved dc-dc topologies were proposed, developed, and carefully studied, among them are unidirectional and bidirectional dc-dc converters for wide range in industrial application, for instance, electric vehicles, photovoltaic, fuel cells, renewable sources, hybrid systems, and battery power supplies. [1][2][3][4][5][6][7][8][9][10] The conventional dc-dc buck converter is widely used because of its practical function (output voltage reduction) and the simplicity of the topology, which is characterized without isolation and the low number of components. On the other hand, it is not suitable in applications that require a voltage gain above 0.8, due to the need of the operations with very high duty cycle values (duty cycle higher than 80%).…”
Section: Introductionmentioning
confidence: 99%